2022
DOI: 10.1007/s12144-022-03705-8
|View full text |Cite
|
Sign up to set email alerts
|

Face masks inhibit facial cues for approachability and trustworthiness: an eyetracking study

Abstract: Wearing face masks during the Covid-19 pandemic has undeniable benefits from our health perspective. However, the interpersonal costs on social interactions may have been underappreciated. Because masks obscure critical facial regions signaling approach/avoidance intent and social trust, this implies that facial inference of approachability and trustworthiness may be severely discounted. Here, in our eyetracking experiment, we show that people judged masked faces as less approachable and trustworthy. Further a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 45 publications
(121 reference statements)
1
10
0
Order By: Relevance
“…The mask, reducing the available information in the lower part of the face, might lead the participants to focus more on the upper part of the face (Barrick et al, 2021; Freud et al, 2020), which would be ineffective in recognizing these emotions. These interpretations are congruent with eye movements and gaze tracking studies showing increased focalization duration and number of fixations on the upper part of masked faces compared to unmasked faces, during tasks assessing judgments of trustworthiness and approachability (Bylianto & Chan, 2022) or during facial identity recognition tasks (Chen et al, 2023; DeBolt & Oakes, 2023; Hsiao et al, 2022). However, to our knowledge, no study using this methodology has been conducted in order to explore more objectively the changes of strategies involved in recognizing the emotions of faces wearing a mask.…”
Section: Discussionsupporting
confidence: 80%
“…The mask, reducing the available information in the lower part of the face, might lead the participants to focus more on the upper part of the face (Barrick et al, 2021; Freud et al, 2020), which would be ineffective in recognizing these emotions. These interpretations are congruent with eye movements and gaze tracking studies showing increased focalization duration and number of fixations on the upper part of masked faces compared to unmasked faces, during tasks assessing judgments of trustworthiness and approachability (Bylianto & Chan, 2022) or during facial identity recognition tasks (Chen et al, 2023; DeBolt & Oakes, 2023; Hsiao et al, 2022). However, to our knowledge, no study using this methodology has been conducted in order to explore more objectively the changes of strategies involved in recognizing the emotions of faces wearing a mask.…”
Section: Discussionsupporting
confidence: 80%
“…However, it is possible that, with ongoing mask exposure, people may learn to better cope with masks. This notion is supported by eye-tracking data that suggests shifts in attention to different facial areas when the mask is present ( 26 ; 27 ). This is particularly interesting as we can speculate that, with more time into the pandemic or mask-wearing practices in general, less pronounced mask effects on emotional mimicry may be expected as perceivers may shift their attention to the eye region.…”
Section: Face Masks and Emotion Perceptionmentioning
confidence: 77%
“…Rather, masks reduced the difference between high and low trustworthy faces, with low trustworthy faces increasing and high trustworthy faces decreasing in perceived trustworthiness. By obstructing cues normally used to judge trustworthiness and diverting attention to less diagnostic facial cues ( Bylianto & Chan, 2022 ), high and low trustworthy faces appear more similar in trustworthiness. Even for masked faces, though, there was a significant difference between high and low trustworthiness faces, indicating that facial cues other than those covered by a mask are used to judge trustworthiness.…”
Section: Discussionmentioning
confidence: 99%
“… Oldmeadow and Koch (2021) and Marini et al (2021) found low trustworthy faces received a significant boost in trustworthiness when masked, whereas high trustworthy faces did not. Bylianto and Chan (2022) found faces with a happy expression were rated lower in trustworthiness when masked than unmasked. Thus, there is some evidence that masks affect perceived trustworthiness by obstructing facial cues normally used to make such judgments, but the precise nature of this effect is unclear.…”
mentioning
confidence: 94%
See 1 more Smart Citation